2014
DOI: 10.1186/1471-2318-14-138
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment for people with dementia: a systematic review of systematic reviews of pain assessment tools

Abstract: BackgroundThere is evidence of under-detection and poor management of pain in patients with dementia, in both long-term and acute care. Accurate assessment of pain in people with dementia is challenging and pain assessment tools have received considerable attention over the years, with an increasing number of tools made available. Systematic reviews on the evidence of their validity and utility mostly compare different sets of tools. This review of systematic reviews analyses and summarises evidence concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
210
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(213 citation statements)
references
References 45 publications
2
210
1
Order By: Relevance
“…Much of the literature concerned with the assessment and management of pain for people with cognitive impairment has focused on the development and validation of observational instruments designed for the purpose of assessment. 54 A number of studies have shown that these tools are not often used in clinical practice, a finding that was supported in our data. This may be because the tools do not facilitate the rapid creation of the 'overall picture of pain' and, therefore, do not assist clinicians with their decision-making about pain in this vulnerable group of patients.…”
Section: For Researchsupporting
confidence: 89%
See 1 more Smart Citation
“…Much of the literature concerned with the assessment and management of pain for people with cognitive impairment has focused on the development and validation of observational instruments designed for the purpose of assessment. 54 A number of studies have shown that these tools are not often used in clinical practice, a finding that was supported in our data. This may be because the tools do not facilitate the rapid creation of the 'overall picture of pain' and, therefore, do not assist clinicians with their decision-making about pain in this vulnerable group of patients.…”
Section: For Researchsupporting
confidence: 89%
“…It presents a thorough synthesis of current systematic review literature concerning the psychometric properties and clinical utility of pain assessment tools for the assessment of pain in adults with dementia, and provides a detailed picture of the state of the field in the complex task of assessing pain. 54 For ease of reference, in this report we refer to our systematic review of systematic reviews as a 'meta-review'. We call the systematic reviews considered for inclusion in the meta-review 'reviews', and refer to publications included in the reviews as 'studies'.…”
Section: Introductionmentioning
confidence: 99%
“…In order to assist with the assessment process a number of assessment tools have been developed. These include simple rating scales for self-reporting of pain as well as tools to structure the observation of behavioural cues as a method for identifying the presence of (and changes in) pain in patients with dementia and other cognitive impairments (Corbett et al, 2012, Lichtner et al, 2014. Despite the abundance of such tools (Lichtner et al, 2014), many studies have highlighted that nurses do not use them in practice, preferring to rely on simple questioning (Manias, 2012) and their (Parke, 1998) or that a patient may be experiencing pain (Parke, 1998)[p26].…”
Section: Pain Assessment As a Judgement Processmentioning
confidence: 99%
“…15 Interestingly, observational pain assessments utilize six domains of behavioral interpretation of pain, highlighted by American Geriatric Society, specifically body language, alterations in mental status, activity variation, facial expression, interactions with others, and negative vocalization. 16 Similarly, painful indicators can include grimacing, moaning, wandering, agitation, inappropriate speech, aggression, restlessness are often useful.…”
Section: Painmentioning
confidence: 99%